Does the change between the native and the prosthetic posterior tibial slope influence the clinical outcomes after posterior stabilized TKA? A review of 793 knees at a minimum of 5 years follow-up - Alhamdi Hassan; Deroche Etienne; Shatrov Jobe; Batailler Cécile; Lustig Sébastien; Servien Elvire (SICOT-J)
Introduction: The understanding of the influence of posterior tibial slope (PTS) on knee kinematics has increased. However, the PTS influence on clinical outcomes remains unclear. The study aimed to evaluate whether a significant change between the native and the prosthetic tibial plateau PTS influences functional results and the risk of complications following total knee arthroplasty (TKA). Methods: This was a retrospective, monocentric comparative study. Clinical and radiological data from 793 knees were collected from a prospective surgical database. Inclusion criteria were patients operated with a posterior-stabilized TKA (PS-TKA) for primary tibiofemoral osteoarthritis, with or without associated patellofemoral osteoarthritis, or osteonecrosis of the femoral condyle or tibial plateau, with a minimum follow-up of 5 years. Range of motion and International Knee Society (IKS) score as well as radiological measurements were collected preoperatively and postoperatively at each follow-up visit. Two groups were composed according to the change in PTS between pre- and post-op (Group 1: ≤10°, n = 703; Group 2: >10°, n = 90). Results: The mean follow-up was 75.5 months ± 9.1. The mean change in PTS from preoperative was 4.96° ± 3.24 in group 1 and 12.7° ± 1.87 in group 2. There was no significant difference in the mean IKS Knee subscore (89.5 ± 10.7 and 89.7 ± 10.2, p = 0.89) and mean IKS Function subscore (88.2 ± 15.7 and 86.3 ± 16.6, p = 0.33) in groups 1 and 2, respectively. Postoperative maximum flexion was very satisfactory in both groups with no clinically relevant difference (120.0 ± 11.9 and 123.0 ± 8.3, p = 0.026). The complication rate was 5.0% (n = 40) (5.5% in group 1; 1.1% in group 2; p = 0.07) while the most common complication requiring further procedure was deep infection (n = 9, 1.1%) and the second most common was stiffness (n = 6, 0.8%). Discussion: PTS did not influence postoperative maximum flexion or clinical scores and was not associated with a higher complication rate at a minimum 5-year follow-up after PS-TKA.